Simulation of Dispersion Modeling of 137Cs for the Possible Leakage of Malaysia’s Nuclear Power Plant Operation - M Muslim; F. I. Maulana; H. Suseno; S. Y. Wulandari (PPIKSN-BATAN, 2022)
The world’s energy needs increase in line with population growth. One alternative to overcome this problem is the construction of a nuclear power plant, a source of energy that is cheap, clean, and safe. Malaysia has a plan to construct nuclear power plants by 2025, which is located close to Indonesian waters. This study aimed to determine the distribution model of 137Cs radionuclide released by the nuclear power plant in the event of a leak in east coast of Peninsular Malaysia and its impact on the presence of 137Cs in Indonesian waters. A quantitative method was used in this study with a scenario 2D modeling using hydrodynamics module and transport module in MIKE software. The results showed that the highest concentration of 137Cs would be found in the area around the nuclear power plant with a value of 1011 PBq/m3, then it would decrease through diffusion and advection processes. On the 15th day, the spread of 137Cs would reach Indonesian waters with a distance of up to 76 km and would expand on the 30th day with a distance of up to 130 km from the released source. The movement of 137Cs follows the dominant current pattern due to its nature. The presence of 137Cs in Indonesian waters after the 15th and 30th days would reach a value of 1 Bq/m3 due to advection and diffusion processes.